2018
DOI: 10.1186/s12964-018-0269-3
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells and mast cell tryptase enhance migration of human lung fibroblasts through protease-activated receptor 2

Abstract: BackgroundMast cells may activate fibroblasts and contribute to remodeling processes in the lung. However, the mechanism behind these actions needs to be further investigated. Fibroblasts are major regulators of on-going remodeling processes. Protease activated receptor 2 (PAR2) expressed by fibroblasts may be activated by serine proteases, such as the mast cell mediator tryptase. The objective in this study was to investigate the effects of mast cells and specifically mast cell tryptase on fibroblast migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 55 publications
4
38
0
Order By: Relevance
“…To study the effect of tryptase and chymase on fibroblast migration, tryptase (75 ng/mL) and chymase (1 ng/mL) were added to HFL-1 cells. In line with our previous data [ 19 ], tryptase significantly enhanced the migratory capacity of fibroblasts at 24 h ( p = 0.001), 48 h ( p = 0.001) and 72 h ( p = 0.001), whereas chymase did not show any significant effect on fibroblast migration ( Figure 3 a). Higher concentration of chymase (10 and 100 ng/mL) appeared to be toxic, where the cells detached from the cell culture plastic plate and migration could not be observed (data not shown).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…To study the effect of tryptase and chymase on fibroblast migration, tryptase (75 ng/mL) and chymase (1 ng/mL) were added to HFL-1 cells. In line with our previous data [ 19 ], tryptase significantly enhanced the migratory capacity of fibroblasts at 24 h ( p = 0.001), 48 h ( p = 0.001) and 72 h ( p = 0.001), whereas chymase did not show any significant effect on fibroblast migration ( Figure 3 a). Higher concentration of chymase (10 and 100 ng/mL) appeared to be toxic, where the cells detached from the cell culture plastic plate and migration could not be observed (data not shown).…”
Section: Resultssupporting
confidence: 93%
“…This could be due to the presence of both chymase and tryptase in LAD2 cells ([ 30 ]. We have previously shown that mast cells and tryptase enhanced the migratory capacity of fibroblasts, which was attenuated by a PAR2 antagonist, confirming that the mechanism behind the induced migration of fibroblasts involve PAR2 activation [ 19 ], as supported by other studies [ 22 ]. In the present study, tryptase enhanced fibroblast migration.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This enzyme exerts a fibrogenic activity, by triggering collagen production by the fibroblasts ( Akers et al, 2000 ; Levi-Schaffer and Piliponsky, 2003 ). Although its role, as a mediator of the fibrotic process, has been analyzed in a few studies ( Kondo et al, 2001 ; Bagher et al, 2018 ), further studies are required to increase the knowledge on its functions and to explore the possibility of using inhibitors targeting the enzyme for an antifibrotic therapeutic intervention. Furthermore, the contribution of plasminogen activator inhibitor-1 (PAI-1) to fibrosis progression through the activation of mast cells has recently emerged.…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…Their location in the dermis, their ability to release vasoactive and proinflammatory substances, and the expression of IgE receptors on their surfaces imply that they have important roles in the immunity of the skin to infectious or harmful agents (132)(133)(134). Mast cells are probably involved in the mechanisms of fibroblast proliferation, blood flow control, and angiogenesis (135)(136)(137)(138)(139). These functions are implicated in extracellular matrix remodeli and in the cicatricial (scarring) and fibrotic processes associated with skin lesions (Table 1) (139).…”
Section: Basophils and Mast Cellsmentioning
confidence: 99%